Le bloc-diagramme : une clé de compréhension des représentations du paysage chez les agriculteurs ? Mise au point d’une méthode d’enquête préalable à une gestion concertée du paysage en Artense (Massif central français) - Yves Michelin (Unité Mixte de Recherche 8504 Géographie-cités, 2000)
3D diagrams that sum up the different kinds of landscape of the middle mountain plateau of Artense (French Massif Central) have been used to analyze landscape opinion of 5 farmers living in this area. 3 D drawing is a very good tool to help farmers explain how they use their plots and where they locate their different kinds of activity (grazing, hey production, manuring, bush clearing...). By this way, they are able to precise on the drawing the landscape elements (trees, stones, buildings) that have been missed or not well located. They can explain which kind of landscape they prefer. For the researcher, it is easier to separate what is determined by technical constraints and what is driven by non-economic factors (tradition, esthetic preferences...) as far as the farmers' actions are concerned. To produce a method that could be used by non-specialists, we have now to create automatic tools to produce these diagrams.